2021
DOI: 10.1177/15330338211041264
|View full text |Cite
|
Sign up to set email alerts
|

EV PD-L1 Contributes to Immunosuppressive CD8+ T Cells in Peripheral Blood of Pediatric Wilms Tumor

Abstract: Wilms tumor (WT) is the most common renal cancer and the most prevalent abdominal cancer in children. Children with recurrent or progressive forms of WT could benefit from novel immune-targeted approaches. While the immune status of these patients, especially the immunosuppression of peripheral T cells, was rarely reported. The present study enrolled a consecutive series of 14 Chinese WT children and 14 age- and gender-matched healthy controls. We demonstrated that plasma extracellular vesicular (EV) PD-L1 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…But there are few reports of childhood tumours. Previous studies have shown that a significant increase in plasma EV PD-L1 in WT patients contributes to the immunosuppression of peripheral CD8+ T cells (23). This suggests that nephroblastoma also has immunosuppression similar to that in adult tumors.…”
Section: Discussionmentioning
confidence: 92%
“…But there are few reports of childhood tumours. Previous studies have shown that a significant increase in plasma EV PD-L1 in WT patients contributes to the immunosuppression of peripheral CD8+ T cells (23). This suggests that nephroblastoma also has immunosuppression similar to that in adult tumors.…”
Section: Discussionmentioning
confidence: 92%
“…In Wilms tumor, however, a single study focused on the analysis of EV-expressed immune checkpoint molecule PD-L1 as a Wilms tumor progression marker. When evaluating PD-L1 levels on plasma EVs from fourteen Wilms tumor patients [ 24 ], PD-L1 appeared significantly correlated with CD8 + T cell function inhibition. However, the study has weak spots; for example, no change was observed in some of the effector T cell markers when T cells were co-cultured with PD-L1 EVs of patients, and no correlation between those markers and PD-L1 was observed.…”
Section: Wilms Tumormentioning
confidence: 99%